Synthesis, Infrared and Powder X-Ray Diffraction Studies of Mixed Halogen Sodalites of the Type Na8[AlSiO4]6Cl2-XIX and Na8-XAgX [AlSiO4]6Cl0.52 - BORHADE, A.V.; G. WAKCHAURE, SANJAY (Asian Journal of Chemistry, 2010)
The present work deals with the synthesis of mixed halogen sodalites of the type Na8[AlSiO4]6Cl2-xIx that have been synthesized by using a low temperature hydrothermal technique. Infrared spectroscopy has been used for the confirmation of the framework structure. The structure of mixed halogen sodalite was established by X-ray Rietvelt refinement in the space group P43n . While, a silver containing derivatives, Na8-xAgx[AlSiO4]6Cl0.52I1.48, obtained through aqueous ion exchange method. In the present study more emphasis is given to find out the correlation of Si-O-Al angle and unit cell parameter with concentration of iodide for different sodalites of Na8[AlSiO4]6Cl2-xIx (where, 0 < x < 2).